Optimization of the conditions of cooperation of hybrid solutions of wind farms and solar farms for the area of Poland - Twaróg Bernard (Technical Transactions)
With the increase in the share, with variable production of renewable energy sources in power systems, many studies and expert opinions have appeared in scientific research and the energy market to determine their optimal technological and locational cooperation. Modern Portfolio Theory (MPT) has often been applied in this context. However, some key aspects important in energy planning have not been included in these analyses. This article presents the use of the Markowitz model (Modern Portfolio Theory) in analyzing the hybrid co-option of selected energy sources, assuming two approaches that take into account gross potential and constraints imposed by technological capabilities. The goal is to determine the optimal value of the participation rate of wind farms and solar farms in the energy production co-op assuming the minimization of risk. The value of risk here is determined by a measure of dispersion for the delivery of a certain amount of energy. The results of the analysis are the determination of a map of optimal values of participation factors between the components of the hybrid energy complex for the area of Poland. Analyses were made for gross potential, showing the possibilities of maximum energy production, and for potential limited by technological possibilities. The study used data characterizing the potential of wind energy and solar energy and temperature. The data used in the analyses are publicly available for research purposes. The analyses were supported by graphs and commentary.